PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN PADA MATERI KEGIATAN EKONOMI PEMBELAJARAN IPS SISWA KELAS IV SD - Lisa Oktarika; Nurrohmatul Amaliyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
This study aims to develop learning video media for social studies content on economic activities in grade IV elementary school. This research was conducted using the Research and Development method using the ADDIE model. This research resulted in a feasibility test and student responses to learning video media for social studies content on economic activities for class IV elementary school. This research was conducted at SDN Cantang Jaya class IV as many as 32 students. The data collection method in this research uses a questionnaire directed at media experts and material experts and in the form of questions created to obtain responses from students who are the subjects of this research. The results of validation by media experts got a percentage of 96% who got the "very worthy" category, then validation by material experts got a percentage of 100% who got the "very worthy" category, while the students' responses got a percentage of 93% in the "very worthy" category. Based on the assessment results obtained from the learning video media product for social studies content, economic activity material in grade IV elementary school can be declared "very suitable" for use.